2022
DOI: 10.1002/glia.24262
|View full text |Cite
|
Sign up to set email alerts
|

GABAB receptor agonist baclofen promotes central nervous system remyelination

Abstract: Promoting remyelination is considered as a potential neurorepair strategy to prevent/ limit the development of permanent neurological disability in patients with multiple sclerosis (MS). To this end, a number of clinical trials are investigating the potential of existing drugs to enhance oligodendrocyte progenitor cell (OPC) differentiation, a process that fails in chronic MS lesions. We previously reported that oligodendroglia express GABA B receptors (GABA B Rs) both in vitro and in vivo, and that GABA B R-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
0
7
1
Order By: Relevance
“…The GABAA receptor-mediated signaling pathways obstruct myelin synthesis, their impacts on myelination may alter due to normal and pathological circumstances ( Zonouzi et al, 2015 ). GABAB receptors also play an important role in regulating myelin synthesis and remyelination, as evidenced by studies using GABAB receptor antagonists and agonists ( Pudasaini et al, 2022 ; Serrano-Regal et al, 2022 ). Furthermore, lower levels of GABA in patient brains with neurodegenerative diseases involving demyelination suggest the importance of regulating GABAergic signaling pathways for prevention ( Cawley et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The GABAA receptor-mediated signaling pathways obstruct myelin synthesis, their impacts on myelination may alter due to normal and pathological circumstances ( Zonouzi et al, 2015 ). GABAB receptors also play an important role in regulating myelin synthesis and remyelination, as evidenced by studies using GABAB receptor antagonists and agonists ( Pudasaini et al, 2022 ; Serrano-Regal et al, 2022 ). Furthermore, lower levels of GABA in patient brains with neurodegenerative diseases involving demyelination suggest the importance of regulating GABAergic signaling pathways for prevention ( Cawley et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…OPCs express both the GABAA and GABAB receptors, which allow for GABAergic inhibitory and glutamatergic excitatory regulation ( Zonouzi et al, 2015 ). Modulation of GABA receptors and GABAergic signaling pathways is implicated in the regulation of OPCs development, myelination, and remyelination ( Bai et al, 2021 ; Serrano-Regal et al, 2022 ). In mouse cerebral slices, the presence of endogenous GABA elevated the rate of OPCs and decreased their maturation, an effect that could be nullified by the administration of gabazine, an antagonist of the GABAA receptor ( Hamilton et al, 2017 ).…”
Section: The Role and Molecular Mechanisms Of Neuronal Activity On Re...mentioning
confidence: 99%
See 2 more Smart Citations
“…GABAergic communication seems to be directly correlated with the degree of maturation of OLs and the myelination process ( Serrano-Regal et al, 2020 ). For example, in in vitro experiments the expression of GABA type A (GABA A ) receptors in the OL membrane is controlled by their proximity to neurons ( Arellano et al, 2016 ), whereas in in vivo experiments, potentiation of GABAergic pathways promotes myelination/remyelination of the system in a variety of experimental models and under different pharmacological conditions of modulation, including administration of tiagabine ( Zonouzi et al, 2015 ), ganaxolone ( Shaw et al, 2019 ), baclofen ( Serrano-Regal et al, 2022 ) or n-butyl-β-carboline-3-carboxylate (β-CCB; Cisneros-Mejorado et al, 2020 ). This last example represents a case of great interest because it has been shown that in in vitro experiments β-CCB acts strongly by potentiating GABA A receptor activity in OLs, with no significant effect on the receptor expressed in cortical neurons ( Arellano et al, 2016 ; Cisneros-Mejorado et al, 2020 ; Ordaz et al, 2021 ), a condition that is essential in the development of drugs with potential clinical use for myelination.…”
Section: Introductionmentioning
confidence: 99%